Can Rapid Progression in Nonambulatory Cerebral Palsy Scoliosis Be Predicted Using Humeral Head Ossification?. Issue 1 (January 2021) - Bram, Joshua T.; Flynn, John M.; Karkenny, Alexa J.; Shah, Ronit V.; Talwar, Divya; Baldwin, Keith D.
Abstract : Background: Patients with cerebral palsy scoliosis (CPS) experience higher complication rates compared with idiopathic scoliosis and often present for surgery with larger curves. Prediction of an inflection point for rapid deformity progression has proven difficult. A proximal humerus-based skeletal maturity staging system (HS) has been recently validated and is commonly visible on the posteroanterior radiograph. The authors hypothesize that this system can be used to identify a period at which CPS may progress rapidly, perhaps facilitating discussion of timely surgical intervention. Methods: A retrospective review was conducted for nonambulatory pediatric patients with CPS who presented between 2009 and 2018 at our institution. All patients were considered for inclusion regardless of operative or nonoperative management. Patients who were skeletally mature at initial evaluation or had prior spine surgery were excluded. The authors analyzed radiographs in each HS available. Survival was calculated for cutoffs of 60 and 70 degrees (numbers found to increase intraoperative and postoperative complications for CPS). Results: Eighty-six patients with CPS were identified (54 male individuals). Major curves increased significantly between HS 1 and 2 (27.7 to 46.6 degrees, P =0.009) and HS 3 and 4 (53.1 to 67.9 degrees, P =0.023). The proportion of curves ≥70 degrees were significantly different between HS ( P <0.001), with the greatest increase between HS 3 and 4 (24% to 51%; ≥70 degrees). The largest drop in the 60/70-degree survival curves was between HS 3 and 4. In a subanalysis, 69% of patients with curves ≥40 degrees but <70 degrees in stage 3 would progress ≥70 degrees by stage 4. Conclusions: Identifying a period of rapid curve progression may guide surgical planning before CPS curves become large, stiff, and more difficult to fix. Our findings suggest that humeral skeletal maturity staging is a valuable decision-making tool in neuromuscular scoliosis, with the HS 3 to 4 transition representing the time of the greatest risk of progression. Consider a surgical discussion or shortened follow-up interval for patients with CPS with curves ≥40 degrees who are HS 3. Level of Evidence: Level II.